2012
DOI: 10.1136/bmjopen-2012-001587
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of simple risk markers for early mortality among HIV-infected patients in Guinea-Bissau: a cohort study

Abstract: BackgroundDecisions about when to start an antiretroviral therapy (ART) are normally based on CD4 cell counts and viral load (VL). However, these measurements require equipment beyond the capacity of most laboratories in low-income and middle-income settings. Thus, there is an urgent need to identify and test simple markers to guide the optimal time for starting and for monitoring the effect of ART in developing countries.Objectives(1) To evaluate anthropometric measurements and measurement of plasma-soluble f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 38 publications
(30 reference statements)
1
37
0
Order By: Relevance
“…Other studies performed in Africa have found that mortality was inversely related to the rate of LTFU 3. Several of the LTFU risk factors among patients on ART were similar to the mortality risk factors among African HIV-infected patients as described elsewhere 26 27. If a more thorough follow-up had been performed in the study period, the mortality rate would presumably be higher.…”
Section: Discussionsupporting
confidence: 59%
“…Other studies performed in Africa have found that mortality was inversely related to the rate of LTFU 3. Several of the LTFU risk factors among patients on ART were similar to the mortality risk factors among African HIV-infected patients as described elsewhere 26 27. If a more thorough follow-up had been performed in the study period, the mortality rate would presumably be higher.…”
Section: Discussionsupporting
confidence: 59%
“…suPAR has previously been shown to predict mortality in treatment‐naïve HIV‐1‐infected patients . In HIV‐patients initiating ART, mortality was concentrated in the highest suPAR quartile, while patients with a low suPAR level had a low risk of mortality despite low CD4 cell count and low body weight . Thus, suPAR appears to add significant information to other measures of poor prognosis in HIV‐infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,29,30 We further required ART initiation after January 2000 to minimize exposure to nucleoside reverse transcriptase inhibitors, such as zidovudine (AZT), didanosine (DDI), or stavudine (D4T), that are associated with peripheral lipoatrophy. 31-33 …”
Section: Methodsmentioning
confidence: 99%
“…4,7-10 Mechanisms for muscle mass loss in HIV might include systemic chronic inflammation, increased resting energy expenditure, antiretroviral therapy (ART)-related fat redistribution and metabolic syndrome, and the impact of HIV-associated comborbidities. 7,8,11-14 …”
Section: Introductionmentioning
confidence: 99%